2001
DOI: 10.1021/nl015549q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Electron Donor States in N-Doped Carbon Nanotubes

Abstract: Nitrogen doped carbon nanotubes have been synthesized using pyrolysis and characterized by Scanning Tunneling Spectroscopy and transmission electron microscopy. The doped nanotubes are all metallic and exhibit strong electron donor states near the Fermi level. Using tight-binding and ab initio calculations, we observe that pyridine-like N structures are responsible for the metallic behavior and the prominent features near the Fermi level. These electron rich structures are the first example of n-type nanotubes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
518
3
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(553 citation statements)
references
References 31 publications
26
518
3
6
Order By: Relevance
“…For instance, doping with boron introduced acceptor states near the valence band edge 46 while nitrogen-doping added electron donor states near the conduction band edge. 47 N-doped MWCNTs were recently demonstrated to enhance significantly the ammonia decomposition activity of Ru nanoparticles dispersed on their exterior walls. 48 Precise manipulation of the location of heteroatoms either exclusively on interior or exterior walls of CNTs may allow fine-tuning of catalytic properties.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…For instance, doping with boron introduced acceptor states near the valence band edge 46 while nitrogen-doping added electron donor states near the conduction band edge. 47 N-doped MWCNTs were recently demonstrated to enhance significantly the ammonia decomposition activity of Ru nanoparticles dispersed on their exterior walls. 48 Precise manipulation of the location of heteroatoms either exclusively on interior or exterior walls of CNTs may allow fine-tuning of catalytic properties.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The amount of doped nitrogen can be tuned in the range of N/C atomic ratio < 0.1 [98][99][100][101]. A unique feature of the N-doped CNTs synthesized by the AAO template method is that their hollow cores are empty, which is quite different from the bamboo-like structures of the N-doped CNTs by the conventional synthesis methods [95,[106][107][108]. And such N-doped AAO-CNTs show advantage in the filling of foreign matters.…”
Section: Hetero Atom Doping Of the Aao-cntsmentioning
confidence: 99%
“…When an electric field is applied, metal ions in the electrolyte solution migrate and are deposited onto an electrode by passing a current through an electrochemical cell. Therefore, metals can be filled into the cavity of AAOCNTs by using the electrodeposition method under a direct current [41,128,129] or alternating current [106]. In general, a layer of Au is first deposited on the surface of a both-side open AAO film using ion sputtering technique.…”
Section: Electrodepositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that it is possible to alter both mechanical and electronic properties of nanotubes by modifying their side walls physically and chemically (deformations, defects, B-and N-doping, functional side groups). 5,[10][11][12][13][14][15] Furthermore, one can use noncovalently attached supermolecules for isolating CNTs and blocking their self-adhesion scheme in polar solvents. 16,17 Crown ethers and cyclodextrins are interesting molecules in this respect, because they have hydrophobic and hydrophilic parts and tend to attach to organic macromolecules.…”
Section: Introductionmentioning
confidence: 99%